A feasibility study on piezoelectric energy harvesting from the operational vibration of a highway bridge. Issue 2 (January 2023) - Infantes, María; Castro-Triguero, Rafael; Sola-Guirado, Rafael R; Bullejos, David; Friswell, Michael I
Vibration-based energy harvesting represents a clean power technology that can be of interest for application in civil engineering structures. This study focuses on energy harvesting using cantilever piezoelectric devices excited by operational and ambient bridge vibration. The optimal design and analysis of energy harvesters is usually performed using the mean and standard deviation of a response quantity of interest (i.e. voltage) under broadband Gaussian white noise excitation. In this paper, a novel holistic approach to the problem is proposed through the statistics of the voltage of piezoelectric energy harvesters under real measured bridge vibration base excitation. A new semi-analytic expression of the expected power is developed. The solution is based on the closed-form of the frequency response function between the harvester output voltage and the base excitation, and the experimentally measured spectral density of the latter. A study on the influence of the electromechanical coupling of the problem equations is first conducted. Then, a sensitivity analysis of the piezoelectric energy harvester parameters is performed. The critical analysis is developed through a case study of the measured long-term vibrations of a bowstring-arch highway bridge. Both operational and ambient vibration records are considered in the feasibility study. The results show the potential of the semi-analytic expression to evaluate the harvested power of piezoelectric harvesters under operational structural vibration. This is a promising approach to confidently develop future analyses on the power requirements of wireless sensor networks for SHM.